Digital marketing optimization for MSMEs in Tonjong Village, Serang Regency - Ivan Issa Fathony; Ombi Romli (Community Empowerment, 2024)
Digital transformation in Indonesia has encouraged Micro, Small and Medium Enterprises (MSMEs) to adapt to changing times. This community service aims to improve the knowledge and skills of MSMEs in Tonjong Village, Kramatwatu District, Serang Regency regarding digital marketing to promote products. The implementation method consists of the stages of preparation, training, mentoring, and evaluation. The training results show an increase in participants' ability to use social media and marketplace platforms to reach a wider market. The implementation of a digital marketing strategy has proven effective in increasing the visibility and sales of MSMEs. In addition, this activity also contributes to the economic independence of the community, especially for housewives who own businesses.